SUGGESTIBILITY AND SUBSTANCE ABUSE AMONG ADOLESCENTS: EXAMINING THE ASSOCIATION THROUGH STRUCTURAL EQUATION MODELING - Kalsoom, Ume; Malik, Jamil (Journal of Postgraduate Medical Institute, 2020)
Objective: To examine the association between suggestibility and drug abuse while controlling the effect of socio-demographic variables. Methodology: It was a cross sectional survey conducted in three different professional institutes, namely Khyber Medical University, University of Engineering and Technology Peshawar and Ghulam Ishaq khan University Swabi, Khyber Pakhtunkhwa, from March to April 2012. A total of 300 students both male and female in the age range of 19-25 years were enrolled from different programs. Purposive sampling technique was used to collect the data. Demographic Data Sheet, Short Suggestibility Scale (SSS) and Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) were used. The suggestibility scale has a good reliability (i.e., Cronbach's alpha =.85). Spearman's rank correlation test was used to measure the association between the two variables. Results: The correlations analysis presented a negative relationship between age and substance use and a positive correlation between substance use and living status suggesting that young adolescents and adolescent living in their homes were more vulnerable to substance use. Suggestibility appeared to have the strongest relationship with drug abuse (i.e., rs =-.47, p <0.01) presenting it as one of the key indicators of drug abuse. Conclusion: Age, living with family and suggestible personality traits are vulnerability factors for substance abuse.